Variation in physiology and water use efficiency among Musa balbisiana genotyes in response to drought - Delfin, Evelyn F.; Ocampo, Eureka Teresa M.; Dela Cueva, Fe M.; Damasco, Olivia P.; Herradura, Lorna E.; Dinglasan, Eric G.; Gueco, Lavernee S.; Dela Cruz, Felipe S., Jr.; Molina, Agustin B. (2011)
Musa balbisiana genotypes are reported to have traits that confer field drought tolerance. However, the natural variation in these traits is relatively unknown, and therefore cannot be exploited in breeding programs. This paper reports on the variation of the effects of drought on the growth and physiology of twenty-nine wild and edible M. balbisiana genotypes from the Philippine and Southeast Asian germplasm collection. Two batches of tissue-culture derived seedlings were potted out and established in the greenhouse from March to May 2010. Drought was imposed after three months. Pots were weighed at soil field capacity and periodically during progressive drought. Stomatal openings closed on the third and sixth day after water was withheld in April and May 2010, respectively. The stomatal conductance was significantly affected by the interaction between genotype and stress condition. Water use efficiency (WUE) differed significantly among genotypes during drought, which ranged from 8.9 to 19g dry matter kg-1 water used. Genotypic differences in relative water content (RWC) were observed in April 2010 trial, but not in May 2010 when temperatures were much higher. RWC ranged from 80-96% even when leaves were already wilted. Genotypic variation in plant and root growth and accumulation of dry matter were also observed.
Keywords: Bananas; Drought-tolerant plants